Traditional Minangkabau disaster mitigation in the Semangko Fault in West Sumatra based on ecological site myths - Anwar Khairil; Khallifhatul Khanh Varhanno; Qurratu Ayuni Khanh Vitrya; Narny Yenny (E3S Web of Conferences)
This paper discusses traditional Minangkabau disaster mitigation based on the myths of Minangkabau ecological sites located in the Semangko Fault area in West Sumatra. Traditional communities believe in myths as a force that guides their relationship with ecological sites. Natural signs conveyed in myths serve as guidelines for the community in disaster mitigation. This belief has the consequence that the community must adhere to it. Myths may deviate from beliefs to the superstructure and, vice versa, originate from conventions so that they become superstructure. Therefore, through a qualitative study, myths related to ecological sites and their meanings are documented about community disaster mitigation in the Semangko Fault area. The analysis was conducted using the perspective of cultural materialism. It was found that myths are the superstructure of ecological sites that regulate human interaction with the environment; myths embody past local experiences of natural disaster events; myths become a reference for disaster mitigation management that is familiar in local communities. Recommendations in disaster management should consider myths in disaster mitigation.